(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the level of satisfaction among breast cancer inpatients at Thanh Hoa Oncology Hospital in 2024 and to identify associated factors. Methods: A cross-sectional descriptive study was conducted on 200 in patients undergoing breast cancer treatment. Data collection techniques and quantitative tools were applied in accordance with Decision No. 56/QD-BYT dated 08/01/2024, issued by the Ministry of Health, on promulgating standardized forms and guidelines for surveying patient. Satisfaction assessment criteria for each sub-item on the Likert scale < 4 points is not satisfied and ≥ 4 points is satisfied. The association was analyzed using OR and 95%CI. Results: The results showed that the proportion of inpatients receiving breast cancer treatment at Thanh Hoa Oncology Hospital who were satisfied with the medical services was high (91%), with an average overall satisfaction score of 4.18/5 points. Multivariable regression analysis indicated that, compared to patients living more than 10 km from the hospital, those residing within 5 km and 5-10 km had significantly lower levels of overall satisfaction, with OR = 0.036; 95%CI: 0.003-0.379 and OR = 0.056; 95%CI: 0.006-0.495, respectively. Conclusion: The overall satisfaction rate of breast cancer patients treated as inpatients at Thanh Hoa Oncology Hospital is very high (91%). Patients living far from the hospital have a higher satisfaction rate with medical examination and treatment services. For further enhance the satisfaction of breast cancer inpatients, the hospital should promptly address issues related to malfunctioning equipment and machinery. Additionally, it is essential to strengthen the management and inspection of restrooms and shower areas in each department.